2022
DOI: 10.5586/asbp.9110
|View full text |Cite
|
Sign up to set email alerts
|

Polish Achievements in Bioactive Compound Production From In Vitro Plant Cultures

Abstract: Plant cell and organ cultures are potential sources of valuable secondary metabolites that can be used as food additives, nutraceuticals, cosmeceuticals, and pharmaceuticals. Phytochemical biosynthesis in various in vitro plant cultures, in contrast to that in planta, is independent of environmental conditions and free from quality fluctuations. Pharmaceutical application of plant biotechnology is of interest to almost all departments of the Faculty of Pharmacy and Institute of Pharmacology in Poland with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…The heterocyclic system of quinolizidine is unique in terms of its chemical structure, and huperzine A (Figure 3) is a potent and reversible acetylcholinesterase inhibitor that is not often described in organic chemistry or phytochemistry 69–71 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterocyclic system of quinolizidine is unique in terms of its chemical structure, and huperzine A (Figure 3) is a potent and reversible acetylcholinesterase inhibitor that is not often described in organic chemistry or phytochemistry 69–71 …”
Section: Resultsmentioning
confidence: 99%
“…68 The heterocyclic system of quinolizidine is unique in terms of its chemical structure, and huperzine A (Figure 3) is a potent and reversible acetylcholinesterase inhibitor that is not often described in organic chemistry or phytochemistry. [69][70][71] Huperzia serrata extract standardized for huperzine A, and also huperzine A itself, has become common ingredients found on the labels of various categories of DS, including nootropics, pre-workouts, and thermogenics. 41,72 Huperzia serrata (with or without standardization to huperzine A) was found on the label of 10 (20%) of the 50 selected DS reviewed.…”
Section: Acetylcholinesterase Inhibitors Including Huperzine Amentioning
confidence: 99%
“…Furthermore, genetic transformation and elicitation using different growth regulators (e.g., methyl jasmonate, yeast extract, and chitosan) have been studied to increase the production of active metabolites and, in consequence, the biological potential of Droseraceae and Nepenthaceae, and it was found that carnivorous plants are susceptible to elicitation [69,74,184,193,195]. For instance, the beneficial effect on naphthoquinones content in the roots of Dr. burmanii and Dr. indica was observed for yeast extract [186,196].…”
Section: Possibility Of Cultivationmentioning
confidence: 99%
“…For this purpose, various types of in vitro cultures have been performed (e.g., shoot, callus, root, and suspension cultures), and various treatments have been used to stimulate the biosynthesis of secondary metabolites (Kikowska et al, 2022). is issue has been discussed in a separate publication (Pietrosiuk et al, 2022).…”
Section: Selected Achievements Of Biotechnological Researchmentioning
confidence: 99%